Drivers' willingness to pay for curb parking (rather than in a garage) - Martijn Kobus; Eva Gutiérrez-i-Puigarnau; Piet Rietveld; Jos Van Ommeren (European Regional Science Association (ERSA), 2012)
Although the growing economics of parking literature almost exclusively focuses on the drivers' choice between curb and garage parking (and the consequences of non-optimal pricing), we are not aware of a substantial literature of revealed-preference studies which examines this choice. As a result, we currently have little or no knowledge to what extent differences between on-street and garage parking prices affect this choice. We introduce and apply an easy-to-implement methodology to estimate drivers' willingness to pay for curb parking (relative to garage parking), using information from administrative data about parking choice and parking duration for one particular city. This kind of administrative data is widely available in many other cities around the world. So, one of the advantages of our methodology is that it easily be reapplied in other cities. In essence, we estimate the effect of parking prices on parking choice (i.e. street or garage), given information about parking durations. Our methodology is based on the observation that the differences in prices for on-street and garage parking depends on parking duration. So, conditional on (anticipated) parking duration, drivers face different pricing schemes. The endogeneity of parking duration is acknowledged in the estimation procedure. We show that drivers' willingness to pay for curb parking (relative to garage parking) is positive and about exteuro 0.35 - 0.58. When we assume a car drivers' value of time of exteuro 5.00 per hour, our results imply that drivers save about 4 - 7 minutes when parking on-street. This seems a reasonable result. Our results also imply that car drivers are rather sensitive to small price differences between street and garage parking, which makes sense as both are close substitutes. For example, if curb parking were only 33 percent cheaper than garage parking, the on-street stock of cars would increase threefold. Our estimates strongly suggest that a parking regime including curb prices that are (slightly) higher than garage prices is welfare improving, in particular because drivers with longer parking durations are induced to use garage parking. : Curb parking, garage parking, parking policy.
Keywords: R41; 330